Physiotherapy in the Ancient Olympics - Παππάς, Αναστάσιος (Πανεπιστήμιο Πελοποννήσου, 2022)
The aim of this study was to demonstrate by conducting a literature review that physiotherapy was practiced in the Ancient Olympics, albeit under a different professional name and that these ancient professionals assisted the athletes prior to their competition and also played a part in the on-field support of the injured athletes, both at the ancient training grounds known as the gymnasia and at Olympia itself, at the Ancient Olympic Games (AOG). During the review of the literature designated by the demarcation lines set out as being the beginning of the AOG in 776BC and ends in 394AD as the last games held in Olympia (IOC, 2022), we find ancient predecessors to the physiotherapists today, known as the aliptes, triveas, and iatroliptes. These therapists initially may have started out as slave labour, but they quickly were acknowledged as being an integral part of the successful Olympic victor’s team. The study also highlights certain artifacts from vases, inscriptions and other ancient references to these professions and to the use of the strigil. A tool seen in ancient times as a piece of equipment carried in the athletes “kit bag”, or hanging in the rooms of the gymnasia or in the hands of the aliptes, triveas, and iatroilptes. It was not just a mundane action to remove the gloios (mixture of sweat, oil and dust), and the strigil was not just a piece of bent bronze, but on the contrary, this special tool was probably a direct predecessor to the Muscle Massage Scraper (MMS) tool used today by modern day physiotherapists and the scraping effect that the athlete received from the action of removing the gloios, brought with it a form of muscle relaxation, lactic acid removal and scar tissue realignment, now seen in modern physiotherapy as a part of the physiological benefits associated with the technique known as Instrument Assisted Soft Tissue Massage (IASTM). A comparison of these tools and techniques used by the modern day physiotherapist will be shown to be very similar, if not the same tools (origin) and techniques also used by their ancient predecessors, albeit under different names. The use of photographic artifacts from the past, compared to modern day physiotherapy photographs support the argument that physiotherapy did exist in the ancient Olympics albeit under different names such as the aliptes, triveas, and iatroliptes and not only the techniques of massage used back at the AOG were techniques used by physiotherapists today, but the MMS tool is the modern day strigil used in the Ancient Olympics.
Keywords: Φυσικοθεραπεία - Ελλάδα - Ιστορία; Ολυμπιακοί αγώνες (Αρχαίοι) - Ιστορία; Τραυματισμοί στον αθλητισμό - θεραπεία και άσκηση; Φυσικοθεραπεία - Ελλάδα - Ιστορία; Αθλητικό μασάζ; Χειροπρακτική (Θεραπευτική); Physical therapy - Greece - History; Olympics (Ancient) - History; Sports injuries - Exercise therapy; Physical therapy - Greece- History; Sports massage; Manipulation (Therapeutics); Massage therapy; Iatroliptes; Physiotherapy; Ancient Olympics; Aliptes; Triveas; Strigil